The crystal structure of 4-chloro-thiophenol, C6H5ClS - Manana Pholani; Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures)
C6H5ClS, monoclinic, P21/n (no. 14), a = 5.7461(2) Å, b = 9.7601(4) Å, c = 5.7466(3) Å, β = 95.869(2)°, V = 320.59(2) Å3, Z = 2, Rgt(F) = 0.0216, wRref(F2) = 0.0545, T = 200 K.